The effect of using recreational mathematics on the mathematical achievement of third graders and visual-spatial intelligence (Journal of Misan Researches, 2021)
The current research aims to identify (the effect of using the recreational mathematics method on the mathematical achievement of third-grade students and their visual-spatial intelligence).In order to verify the objective of the research, the researcher formulated the following two null hypotheses:• There is no statistically significant difference at the significance level (05.0) between the average scores of the experimental group students who study mathematics using recreational mathematics, and the average scores of the control group students who study the same subject in the usual way.• There is no statistically significant difference at the level of significance (0.05) between the average scores of the visual-spatial intelligence test among the experimental group students who study mathematics using recreational mathematics, and the average scores of the visual-spatial intelligence test among the students of the control group who study the same subject in the usual way. .- The experiment was applied to the third graders of primary school at Sukar Al-Qasab Primary School for Boys affiliated to the Directorate of Education in Maysan Governorate and for the first semester of the academic year (2016-2017)- The researcher adopted the experimental design with the first two groups, experimental and the second control, and the number of the research sample students was (56) students from the third grade of primary school, distributed between two divisions, Division A includes (30) students and Division B includes (26) students.- Division (A) represented the experimental group that was taught by the recreational mathematics method, and Division (B) represented the control group that was taught in the usual way.- The two groups were rewarded with variables (previous information of students, chronological age in months, previous mathematical achievement).- The researcher prepared an achievement test to measure the achievement of the students of the two groups in mathematics after completing the application of the experiment, consisting of (30) paragraphs, measuring the levels of remembering, comprehension, and application.The validity of its content was verified, by presenting it to a group of specialists, then it was applied to an exploratory sample to ensure the clarity of its paragraphs, its stability, the discriminatory strength of its paragraphs, its difficulty factor, and the effectiveness of its alternatives.- To measure the students' visual-spatial intelligence, the researcher adopted a ready-made test prepared by (Marwa Khader, 2017).The data was treated statistically by using the t-test for two independent samples.The results showed:• The students of the experimental group who studied using the recreational mathematics method outperformed the students of the control group who studied in the usual way in the achievement test for mathematics.• The students of the experimental group who studied using the recreational mathematics method outperformed the students of the control group who studied in the usual way in the test of visual-spatial intelligence. In light of the results of the current research, the researcher recommended• Adopting the recreational mathematics method in teaching mathematics in the third grade of primary school• Training primary school teachers through training courses on how to use the recreational mathematics method.• The necessity of focusing the mathematics curricula in the Ministry of Education on adopting modern strategies, including recreational mathematics, and emphasizing the use of modern strategies